2014
DOI: 10.1007/jhep06(2014)091
|View full text |Cite
|
Sign up to set email alerts
|

Bootstrapping the O(N ) vector models

Abstract: We study the conformal bootstrap for 3D CFTs with O(N ) global symmetry. We obtain rigorous upper bounds on the scaling dimensions of the first O(N ) singlet and symmetric tensor operators appearing in the φ i × φ j OPE, where φ i is a fundamental of O(N ). Comparing these bounds to previous determinations of critical exponents in the O(N ) vector models, we find strong numerical evidence that the O(N ) vector models saturate the bootstrap constraints at all values of N . We also compute general lower bounds o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
606
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(639 citation statements)
references
References 65 publications
32
606
0
1
Order By: Relevance
“…While it is difficult to solve these constraints exactly in d > 2, the recent reformulation of the bootstrap uses unitarity to rephrase the constraint problem as a convex optimization problem, which can be numerically solved to get bounds on the CFT data in any number d of spacetime dimensions (see, for example, ). In several cases [18,29,35,38], these bounds have featured kinks that are believed to be located very close to known CFTs. The conformal bootstrap has therefore allowed these known CFTs to be studied nonperturbatively.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…While it is difficult to solve these constraints exactly in d > 2, the recent reformulation of the bootstrap uses unitarity to rephrase the constraint problem as a convex optimization problem, which can be numerically solved to get bounds on the CFT data in any number d of spacetime dimensions (see, for example, ). In several cases [18,29,35,38], these bounds have featured kinks that are believed to be located very close to known CFTs. The conformal bootstrap has therefore allowed these known CFTs to be studied nonperturbatively.…”
Section: Introductionmentioning
confidence: 82%
“…A recent notable application of these techniques has been to CFTs with global O(N ) symmetry in d = 3 [18]. This class of CFTs are of interest because they include the critical O(N ) vector model, which has several physical applications for d = 3 and N ≤ 3.…”
Section: Introductionmentioning
confidence: 99%
“…The seminal work [8] proposed an efficient numerical procedure for extracting information about the space of all conformal field theories, and has been followed by many other works in a variety of contexts [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Similarly, the studies [24][25][26][27] have shown that it is even possible to analytically derive completely generic constraints on the spectrum of CFTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent numerical studies [49][50][51][52][53] have shed more light on the non perturbative regime of the O(N ) models where they have showed that it is possible to obtain results of the dimensions of certain operators for finite N case which resembles realistic models e.g the Ising model. Meanwhile, on the analytical side, the authors of [54] have shown that it is…”
Section: Introduction and Summary Of Resultsmentioning
confidence: 99%
“…The details can be found in [45][46][47][48][49][50][51][52][53]61]. We focus on theories containing a scalar field φ i in the fundamental representation of O(N ) in d = 4.…”
Section: O(n ) Fundamentalsmentioning
confidence: 99%